A Review of the Pacific Media Landscape: A Baseline Study. (December 2016) - Papoutsaki, Evangelia; Thomas, Verena; Horst, Heather; Tacchi, Jo; Noske-Turner, Jessica; Eggins, Joys
This article draws upon the Pacific Media Assistance Scheme (PACMAS) State of Media and Communication Report to examine the implications of a changing media landscape for journalism practice in the Pacific region. The report contributes to an understanding of the diverse media and communications environments in the Pacific Islands (PI) region and captures aspects of the variations both in media, and in context, across and within the 14 Pacific Islands countries. This article highlights the need for synergies in the Pacific Islands to strengthen legislation, capacity-building initiatives and content production in a fast-changing digital environment.